2019
DOI: 10.1007/s10616-018-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase activity of Wharton jelly mesenchymal stromal cells: isolation and characterization

Abstract: Mesenchymal stromal cells (MSCs) are promising tools in regenerative medicine and targeted therapies. Although different origins have been described, there is still huge need to find a valuable source harboring specific subpopulations of MSCs with precise therapeutic functions. Here, we isolated by fluorescence activated cell sorting technique, two populations of Wharton's jelly (WJ)-MSCs based on their aldehyde dehydrogenase (ALDH) activity. Two different ALDH activities (low vs. high) were thus observed. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
5
0
1
Order By: Relevance
“…Transcriptomic analysis demonstrated that PAFAH1B1 was downregulated by osteogenic BMPs in MSCs [ 31 ]. Besides that, ALDH + WJ-MSCs were found to express higher osteogenic genes such as RUNX2 , OSX and OPN [ 32 ]. Nallamshetty et al [ 33 ] demonstrated that during primary MSCs’ osteoblastogenesis, ALDH1A1 was also expressed besides bone marker alkaline phosphatase (ALP).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis demonstrated that PAFAH1B1 was downregulated by osteogenic BMPs in MSCs [ 31 ]. Besides that, ALDH + WJ-MSCs were found to express higher osteogenic genes such as RUNX2 , OSX and OPN [ 32 ]. Nallamshetty et al [ 33 ] demonstrated that during primary MSCs’ osteoblastogenesis, ALDH1A1 was also expressed besides bone marker alkaline phosphatase (ALP).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that ALDH + sorted stem cells displayed a major hypoxia response compared to ALDH − stem cells, increasing of HIF-1α and HIF-2α. Moreover, ALDH + stem cells exhibited an increased mRNA expression of stemness correlated genes Oct-4, Nanog, Sox-2, and Rex-1 compared to ALDHcells [166].…”
Section: Hif Role In Stemnessmentioning
confidence: 94%
“…HIF capability to preserve stemness could be even correlated with aldehyde dehydrogenase (ALDH) activity as observed in Wharton's Jelly stem cells [166]. Adipose-derived stem cells [167], foreskin-derived mesenchymal stromal cells [168], and for bone marrow mesenchymal stromal cell [169].…”
Section: Hif Role In Stemnessmentioning
confidence: 99%
“…Экспрессия ALDH высокая в жизнеспособных клетках-предшественницах различных линий, включая гемопоэтические, эндотелиальные, мезенхимные и нейральные [9][10][11][12]. В исследованиях последних лет показана стволовая природа мезенхимных клеток жировой ткани [13], вартонова студня пуповины [14], кожи [15], экспрессирующих ALDH. В то же время практически отсутствуют данные о количестве и динамике содержания ALDH-позитивных (ALDH+) элементов в культуре МСК костного мозга доноров и возможной взаимосвязи с показателями скорости роста культуры.…”
Section: Introductionunclassified